2017
DOI: 10.1002/ldr.2829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochar properties on soil conditions and agricultural sustainability: A review

Abstract: This review summarizes the influences of pyrolysis conditions and feedstock types on biochar properties and how biochar properties in turn affect soil properties. Mechanistic evidence of biochar's potential for enhancing crop productivity, carbon sequestration, and nutrient use efficiency are also discussed. The review identifies the knowledge gaps, limitations, and future research directions for large‐scale use of biochar. Both pyrolytic parameters and feedstock types are considered to be the main factors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(106 citation statements)
references
References 295 publications
(384 reference statements)
5
100
1
Order By: Relevance
“…This study observed that the application of biochar to soil slightly increased soybean shoot biomass and grain yield, but the effect was not significant. In several recent studies, it has also been reported that biochar had no significant effect on plant growth or yield [44][45][46][47]. Joseph et al reported that the interaction of biochar with environmental conditions is important to determine the contrasting effects of biochar on plant growth [48].…”
Section: Plant Growthmentioning
confidence: 99%
“…This study observed that the application of biochar to soil slightly increased soybean shoot biomass and grain yield, but the effect was not significant. In several recent studies, it has also been reported that biochar had no significant effect on plant growth or yield [44][45][46][47]. Joseph et al reported that the interaction of biochar with environmental conditions is important to determine the contrasting effects of biochar on plant growth [48].…”
Section: Plant Growthmentioning
confidence: 99%
“…Water saving and ecological restoration are two strategies to adapt crop production to adverse conditions (Al‐Wabel et al, ; Huang et al, ). Water saving includes a variety of management strategies that reduce the use or enhance the water use efficiency under drought stress (Blum, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of information on soil enzyme activities and consequently nutrient availability in the deeper (>20‐cm) soil layers and the cumulative effect of repeated annual applications of PAM. Some recent studies reported the response of soil microbiological properties as affected by agronomic management practices such as biochar application (Al‐Wabel et al, ) and tillage systems (Hsiao, Sassenrath, Zeglin, Hettiarachchi, & Rice, ). Soil enzyme activity has been cited as a potential bio‐indicator of soil microbiological activity due to its highly sensitive response to temporal variations of soil health (Gil‐Sotres, Trasar‐Cepeda, Leirós, & Seoane, ; Li et al, ; Schloter, Dilly, & Munch, ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is called retention capacity and is important to store nutrients in a plant-available form. It has been shown that the weathering of basaltic material increases the cation exchange capacity, leading to an increased retention of nutrients (Anda et al, 2013(Anda et al, , 2015. This is especially important for areas in which nutrients from industrial fertilizer material are quickly washed out, e.g., from the deeply weathered soils (e.g., Oxisols) in tropical regions (Leonardos et al, 1987;Ciceri et al, 2017).…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…This may render dryer regions or areas with unfavorable soil physical properties (Basso et al, 2013) usable for bioenergy plants and/or afforestation. There are also indications that improvement of soil hydrology by biochar may increase yield potentials (Akhtar et al, 2014;Xu et al, 2015;Al-Wabel et al, 2018).…”
Section: Soil Hydrologymentioning
confidence: 99%